PENGARUH PENGURANGAN TONGKOL TIDAK BERKEMBANG DAN PEMBERIAN DOSIS NITROGEN TERHADAP HASIL TANAMAN JAGUNG {Zea mays L.) VARIETAS LOKAL SERAYA - Kristina Erniyani; A.A. Made Sudira Djelantik; Sang Made Sarwadana (AGRICA, 2008)
This research conducted to know the effect of decreasing undergrowth stem earn of corn and fertilized corn yield seraya local variety with nitrogen rates and interaction. The experimental factor is decreased unproductive stem earn consist left behind 1 stem earn (Tl), decrease by left behind 2 stem earn (T2) and without a decrease (T3). The second factor is nitrogen dosage by 0,115 and 172,5 kg N/ha. The result of research indicated a real and extremely real interaction between both of treatment factor (T x N) only happen on the amount of variable seed per line and amount of seed per crop. Treatment without decreasing undergrowth stem earn (T3) caused highly weight dry seed oven per hectare is 2,67 ton and lowest on decreasing undergrowth stem earn treatment to left behind 1 stem earn (Tl) is 1,81 ton. Nitrogen treatment 115kg/ha (N2) caused highly weight dry seed oven 2,97 ton/ha and lowest 1,56 ton by 0 kg/ha nitrogen dosage.